Perbandingan Metode Ses Dan Des Dalam Memprediksi Peserta Didik Baru Di Sma Negeri 1 Tual - Asri Samsiar Ilmananda; Ni Putu Dewi Lestari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The amount of students in a school can affect several aspects of the current educational system, such as teacher availability, classroom management, and school amenities. SMA Negeri 1 Tual is is one of the Favorite High Schools in Tual City, Maluku. to forecast the enrollment at SMA Negeri 1 Tual in order to prevent a backlog of students that would impair the quality of the learning environment. The author uses the Single Exponential Smoothing and Double Exponential Smoothing methods in predicting new students. This study compares forecasting techniques in an effort to assist in projecting how many new students SMA Negeri 1 Tual will accept. This research uses a quantitative forecasting approach method. The information utilized comes from the number of students that registered for three different registration categories Zoning, Achievement, and Affirmation at SMA Negeri 1 Tual between 2017-2023 and Microsoft Excel dan Minitab was used to process and analyze the data. The best forecasting values are found in the zoning category using α=0.9, which has a MAPE value of 4%, the achievement category using the constant α=0.6, which has a MAPE value of 2%, and the category affirmation using α=0.6, which has a MAPE value of 3%.